2016
DOI: 10.1111/echo.13226
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Intrinsic Strain Rate Correcting for Pulmonary Wedge Pressure Is Accurate in Estimating Pulmonary Vascular Resistance in Breathless Patients

Abstract: Left atrial strain rate during atrial systole correlates closely with pulmonary capillary wedge pressure and consequently the calculated pulmonary vascular resistance, irrespective of the etiology of PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…Comparing LA diameter, LAVI and LA deformation measures in ATTR amyloidosis patients with or without atrial arrhythmias on Holter ECG, LASRa was the only parameter that was in difference between the 2 groups (p ¼ .006). The reproducibility of LASRa measurements has previously been shown by the authors to be quite satisfactory [15].…”
Section: Predictors Of Atrial Arrhythmiamentioning
confidence: 78%
“…Comparing LA diameter, LAVI and LA deformation measures in ATTR amyloidosis patients with or without atrial arrhythmias on Holter ECG, LASRa was the only parameter that was in difference between the 2 groups (p ¼ .006). The reproducibility of LASRa measurements has previously been shown by the authors to be quite satisfactory [15].…”
Section: Predictors Of Atrial Arrhythmiamentioning
confidence: 78%
“…This might indicate that LASRa is a relatively sensitive marker for PCWP, which is known to be difficult to assess. The use of LASRa, but not LA conduit (LASRe) or reservoir (LASRs) strain rate, as reliable marker for PCWP supports our own previous findings (Tossavainen et al ., ). In contrast, the commonly used markers of raised LA pressure, that is, E/A and E/e’ were significantly less accurate in predicting PCWP.…”
Section: Discussionmentioning
confidence: 97%
“…LASRa, on the other hand, represents cavity deformation during LA contraction, therefore by definition is more directly related to intracavitary pressure changes. We have previously shown that LASRa correlate with PCWP at rest (Tossavainen et al ., ), being the LA strain measure least influenced by LV function (Ramkumar et al ., ). Furthermore, we have shown that LASRa can accurately predict atrial arrhythmia (Henein et al ., ,).…”
Section: Discussionmentioning
confidence: 99%
“…The same group has shown that LA strain may be a superior marker that could not only discriminate all grades of LV diastolic dysfunction vs. normal with excellent areas under the curves but also demonstrate that LA strain is useful for “accurate characterization” of LV diastolic dysfunction . Tossavainen et al showed that in patients with HF, LA strain rate during atrial contraction correlated strongly with pulmonary capillary wedge pressure and the correlation was better than the E/e’ ratio . Brand et al have shown that LV diastolic dysfunction is associated with decreased RA and RV free wall strain.…”
Section: Could Biatrial and Rv Strain Aid In The Diagnosis Of LV Diasmentioning
confidence: 99%
“…Although there is a reportedly plausible association between LA strain and LV filling pressure, such association in the right‐sided heart and the pulmonary artery circuit is less well established. We present here a short report on a possible mechanistic and hemodynamic association between RA strain and right heart catheterization obtained PASP, pulmonary vascular resistance, and RA pressure.…”
Section: Pulmonary Heart Disease and Right Atrial Mechanicsmentioning
confidence: 99%